2007
DOI: 10.1016/j.bbamem.2007.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Aβ ion channels. Prospects for treating Alzheimer's disease with Aβ channel blockers

Abstract: The main pathological features in the Alzheimer's brain are progressive depositions of amyloid protein plaques among nerve cells, and neurofibrillary tangles within the nerve cells. The major components of plaques are Abeta peptides. Numerous reports have provided evidence that Abeta peptides are cytotoxic and may play a role in the pathogenesis of AD. An increasing number of research reports support the concept that the Abeta-membrane interaction event may be followed by the insertion of Abeta into the membra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
193
1
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(204 citation statements)
references
References 108 publications
8
193
1
2
Order By: Relevance
“…More recently, basing our work on an earlier least-energy molecular model of the oligomeric Abeta channel (44 and [supporting information (SI) Fig. S1]), we found that highly selective A␤ channel blockers could be created from polypeptide segments predicted by the model to line the mouth of the A␤ pore (34,(45)(46)(47)(48). Furthermore, these polypeptide inhibitors also proved to be potent inhibitors of A␤ neurotoxicity.…”
mentioning
confidence: 63%
See 1 more Smart Citation
“…More recently, basing our work on an earlier least-energy molecular model of the oligomeric Abeta channel (44 and [supporting information (SI) Fig. S1]), we found that highly selective A␤ channel blockers could be created from polypeptide segments predicted by the model to line the mouth of the A␤ pore (34,(45)(46)(47)(48). Furthermore, these polypeptide inhibitors also proved to be potent inhibitors of A␤ neurotoxicity.…”
mentioning
confidence: 63%
“…In fact, previous data of this sort have contributed to the compelling support for the A␤ calcium channel hypothesis for the pathogenesis of Alzheimer's disease (45). However, with the exception of the other blocking compounds modeled after the amino acid sequences forming the mouth of the Abeta pore (34,(45)(46)(47)(48), the other inhibitors, such as Tris and Zn 2ϩ could be considered somewhat on the less potent side of the concentration/efficacy scale. For example, relatively high concentrations of Tris (1-10 mM) are needed both to block Abeta channels (32) and to protect against neurotoxicity (42).…”
Section: Discussionmentioning
confidence: 99%
“…The predominant ones are Ab-40 ( 90%) and Ab-42 ( 10%). Once produced, Ab-peptides exert their damaging effects both extra-and intra-cellularly (Arispe et al, 2007;Nunan and Small, 2000;Stine et al, 2003;Verdile et al, 2004).…”
Section: Alzheimer's Amyloidogenic Membrane-associated Proteinsmentioning
confidence: 99%
“…First pioneered by Arispe et al (1993), this mechanism is now commonly referred to as the b-amyloid calcium channel hypothesis after its inception in 1994 (Arispe et al, 1994). Readers are referred to a recent review by the same authors, for an indepth discussion on the Ab ion channel-based neurodegenerative mechanism (Arispe et al, 2007). The ion channels would allow excessive calcium influx into the cell, causing destabilization of cellular ionic homeostasis and inducing cell pathophysiology and neuritic degeneration in amyloid diseases (Lin et al, 2001;Quist et al, 2005).…”
Section: Lipid Modulation Of Amyloid Beta Aggregation and Neurotoxicitymentioning
confidence: 99%
See 1 more Smart Citation